Assessing Impact of Health Oriented Aid on Infant Mortality Rates - Ahmed Sadek Yousuf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper examines the relationship between health aid and infant mortality, using data from in total 135 countries (for the purposes of this study, developing countries), between 1975 and 2010. Utilizing both conventional Instrumental Variable and System GMM approaches, a tentative conclusion can be drawn that aid comes to have a statistically significant and positive effect on infant mortality rate, as doubling of aid leads to an approximately 1.3% reduction in infant mortality rates. Thus for an average aid recipient country, doubling per capita aid leads to a reduction of about 790 deaths per million live births in a particular year. This effect, in comparison to the set goals of the Millennium Development Goals, is small and may not be enough to ensure that the MDG targets are met by 2015.
Additional information: This paper is based on the author's MSc dissertation at the University of Nottingham. Title of the original work: Impact of Health Aid on Infant Mortality Rates, also available at EconStor: http://hdl.handle.net/10419/67334
Keywords: F35; C23; C33; I10; 330; Health Oriented Aid; Infant Mortality Rates; Panel Instrumental Variable; System GMM; MDG; Public health insurance; Child mortality; Instrumental variables estimation; Method of moments